Preliminary results on the transverse flow of charged K mesons emitted from Ag+Ag collisions at beam energy of 1.58 GeV/nucleon measured with HADES - Orlinski Jan (EPJ Web of Conferences)
In this contribution, preliminary results on the flow of charged K mesons emitted from semicentral Ag+Ag collisions at a beam kinetic energy of 1.58 GeV/nucleon measured with HADES are presented as v1,2 coefficients mapped in the scaled rapidity – transverse momentum phase space. The coefficients, extracted by fitting a Fourier series to the azimuthal angle distributions, are corrected for the finite resolution of the event plane reconstruction, but not yet for inefficiencies related to the local track density in the detector. The K± flow is compared to the corresponding distributions for protons emitted from the same system. These comparisons suggest a repulsive potential between the K+ and nuclear matter, while conclusions for the K− are not possible to be drawn at this point, due to high statistical uncertainties.